Evaluating Regional Governance - Methodological Concerns and Practical Experiences - Ulrich Dönitz; Jan Fasselt; Stefano Panebianco; Ralf Zimmer-Hegmann (European Regional Science Association (ERSA), 2005)
Since the early 1990s, new forms of regional governance have spread over Western Europe: In many countries, the competencies and ressources of the subnational level have been reinforced (Jessop 1997). In parallel, there has been a shift from hyrarchical modes of government to more flexible, network-based types of governance. These are largely based on the cooperation of public and private actors as well as the civic sector (Benz 2003, Healey 2002 a.o.). Despite its popularity, the regional governance approach has so far only rarely been evaluated systematically. There might be several reasons for this shortcoming. First, the regional governance concept still lacks a clear definition; without knowing what regional governance is, it is hardly feasible to "test” for its outcomes. Moreover, regional governance systems and processes are marked by continuous and rapid transformations. Hence it is difficult to capture their impacts. Finally, the complexity of regional development processes render the assessment of the institutional background a methodological challenge. In the face of these considerations, this paper pursues a threefold objective. First, the authors explain the various needs of evaluating regional governance approaches. These include matters of efficiency as well as cohesion and accountability. Second, the paper discusses the methodological pitfalls and tasks that evaluators need to tackle in order to assess the benefits and weaknesses of regional governance processes . Third, the paper povides an insight into German evaluation experiences in the field, namely some first results from an evaluation of regional cooperation processes in Northrhine-Westfalia carried out at the ILS NRW in Dortmund. The paper concludes by deducing recommendations on how to evaluate regional governance.
Keywords: 330